Noncollinear ferroelectric and screw-type antiferroelectric phases in a metal-free hybrid molecular crystal - Na Wang; Zhong Shen; Wang Luo; Hua-Kai Li; Ze-Jiang Xu; Chao Shi; Heng-Yun Ye; Shuai Dong; Le-Ping Miao (Nature Communications)
Abstract Noncollinear dipole textures greatly extend the scientific merits and application perspective of ferroic materials. In fact, noncollinear spin textures have been well recognized as one of the core issues of condensed matter, e.g. cycloidal/conical magnets with multiferroicity and magnetic skyrmions with topological properties. However, the counterparts in electrical polarized materials are less studied and thus urgently needed, since electric dipoles are usually aligned collinearly in most ferroelectrics/antiferroelectrics. Molecular crystals with electric dipoles provide a rich ore to explore the noncollinear polarity. Here we report an organic salt (H2Dabco)BrClO4 (H2Dabco = N,N’−1,4-diazabicyclo[2.2.2]octonium) that shows a transition between the ferroelectric and antiferroelectric phases. Based on experimental characterizations and ab initio calculations, it is found that its electric dipoles present nontrivial noncollinear textures with 60o-twisting angle between the neighbors. Then the ferroelectric-antiferroelectric transition can be understood as the coding of twisting angle sequence. Our study reveals the unique science of noncollinear electric polarity.